Pemodelan Basis Data Real-Time Monitoring dan Smart Authentication pada Safan Laundry - Shabrina Hikmah Shafiyyah; Tiffana Ryadinka Zylastia; Zatin Niqotaini (GLOBAL SCIENTS PUBLISHER, 2026)
Conventional laundry services face major challenges related to user time inefficiency and clothing security risks during the washing process. This study aims to design a self-service laundry database system that integrates real-time monitoring and smart authentication features to address these issues. The method applied is a structured approach comprising four stages: literature study, requirements analysis, system design, and testing and evaluation. The design produces three database representation models, namely Entity Relationship Diagram (ERD), Conceptual Data Model (CDM), and Physical Data Model (PDM), encompassing six main interrelated entities including user, transaction, payment, machine, usage session, and notification. Real-time monitoring is implemented through the usage session entity that dynamically records machine status, while smart authentication is realized through a unique code mechanism as verification for machine activation and laundry retrieval. Logic testing results indicate that the database design is capable of maintaining data integrity and consistency throughout the entire operational workflow without significant relational conflicts or data redundancy, thus the system is considered ready as a foundation for further technical implementation.